Hydraulic Pressure Management of Yerevan City’s Water Supply Systems - Aram Sahakyan (Journal of Architectural and Engineering Research, 2022)
The system’s excessive pressure management after zoning is essential for improving the existing water supply operation efficiency. Our original research proves that pressure control reduces the leaks in the water supply network, increasing the reliability level of the internal and external networks and saving energy consumed in pumping systems. In recent years, 243 pressure regulating valves (PRV) have been installed in the 97 zones of the expanded water supply network in the Yerevan city (the difference between the levels in the city reaches up to 500 meters) for pressure control in complex terrain conditions.